Sustainable Product Design Strategies for Women Empowerment in Kenya - Matayo, Coletta R. (My University, 2016)
The design of products is a major tool for women empowerment in the world’s developing countries. Women and especially those living in the rural peripheries as well as slum areas, shoulder the burden of the world’s poverty. Fighting poverty in communities requires encompasses empowering women to achieve sustainable development. Women empowerment is crucial for the overall development of a nation and more so developed countries; much has been done to streamline young girls and women by removing barriers to their development. NGOs have been at the forefront in mainstreaming women empowerment through core activities that the women engage in, one such activity being the design and production of craft items. Design and production of items in the line of apparel, basketry, pottery and beadwork has been common among women empowerment initiatives. In countries such as South Africa, product design has been used as a tool for empowering societies through community programmes and projects such as Phumani paper which empowers women economically through production of paper enabling them to fend for their families and educate their children. Product design in simple terms is seen as a wide array of activities that lead to the creation of new items or products. In this regard, production of crafts is seen as a form of product design. However, the products under study in this research will be limited to textile products including but not limited to; apparel, clothing, accessories and home furnishings. Sustainable product design is concerned with social, cultural, economic and environmental impacts of activities carried out in the practice. In this research it is achieved through incentives such as training of the employees, provision of decent jobs to them, provision of sustainable markets for their products, as well as encouraging them to undertake the production process in a sustainable manner through use of environmentally friendly materials such as recycled materials in production. Case study approach was used as it was seen to be the most appropriate approach applied in similar studies in the past. This research critically examined the strategies applied at LifeLine Fashion Initiative by CTC International in Maai Mahiu and James Foundation in Kasarani as well as how sustainable women empowerment has been undertaken. The model can be replicated in other parts of Kenya, Africa and developing nations at large. Case study design approaches have been used to gather information and the results presented in descriptive form complimented by photographs and diagrams.
Keywords: Design of products; Design and production